2015
DOI: 10.4081/ejh.2015.2446
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of CART-containing cells in urinary bladder of rats with renovascular hypertension

Abstract: Recent biological advances make it possible to discover new peptides associated with hypertension. The cocaine- and amphetamine-regulated transcript (CART) is a known factor in appetite and feeding behaviour. Various lines of evidence suggest that this peptide participates not only in control of feeding behaviour but also in the regulation of the cardiovascular and sympathetic systems and blood pressure. The role of CART in blood pressure regulation led us to undertake a study aimed at analysing quantitative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…During the present investigation, CART-immunoreactive neurons have been noted in both types of enteric plexuses within all studied fragments of the esophagus. Till now, the presence of this peptide has been noted in various parts of the peripheral nervous system, such as innervation of gall bladder, urinary bladder, pelvic ganglia, dorsal root ganglia, and many others [29][30][31]. The presence of CART has been also investigated in the GI tract of a wide range of mammal species, including humans [14,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…During the present investigation, CART-immunoreactive neurons have been noted in both types of enteric plexuses within all studied fragments of the esophagus. Till now, the presence of this peptide has been noted in various parts of the peripheral nervous system, such as innervation of gall bladder, urinary bladder, pelvic ganglia, dorsal root ganglia, and many others [29][30][31]. The presence of CART has been also investigated in the GI tract of a wide range of mammal species, including humans [14,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies confirm that the administration of recombinant CART peptide into the right lateral ventricle of the hypothalamus leads to a large decrease in food intake in both lean and obese rats (Larsen et al 2000). Recent studies show that high blood pressure can be a factor that increases CART secretion (Janiuk and Kasacka 2015). In rats with simultaneously stimulated D1 and D2 dopamine receptors intracucumbal injection of CART reduced the effects of psychostimulants (Moffett et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Cocaine-and amphetamine-regulated transcript (CART) has been analyzed for over 20 years. First, CART mRNA was identified in the rats striatum (Douglass et al 1995), and further research has shown that CART peptide is present throughout various regions of the central nervous system (CNS) (Douglass et al 1995, Smith et al 1997, Larsen et al 2003, Fagergren and Hurd 2007, Hubert et al 2008), enteric nervous system (ENS) (Zacharko--Siembida and Arciszewski 2014), peripheral nervous system (PNS) (Zacharko-Siembida and Arciszewski 2014, , Radzimirska et al 2016) and cells in the urinary bladder (Janiuk and Kasacka 2015). The presence of CART in the dense core vesicles of synaptic terminals implies that this peptide acts as a neurotransmitter and/or neuromodulator (Smith et al 1997) and coexists with other biologically active substances (Smith et al 1997, Radzimirska et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the distribution of articles on these subjects during the last five years ( Figure 2 ) may help to understand how the interests of this journal’s authors changed over time, particularly in the most recent time. The articles in Pathology & Experimental Medicine ranged from more than 40% to about 20%, having been very numerous in 2013, 5-15 while progressively decreasing in 2014 16-29 and 2015; 30-40 ; most of these papers were focused on the detection of tumor markers, 11 , 12 , 14 , 16 , 18 , 21 , 23 , 28 , 34 but several were aimed at elucidating the mechanisms of carcinogenesis and tumor progression. 7 , 10 , 13 , 26 , 29 , 33 There was steady interest for developmental investigations and stem cell biology with about 15% of the published articles in the last couple of years: molecular markers of cell differentiation were used to describe the process of placenta formation 41 , 42 and organogenesis, 43-46 and to phenotype stem cells.…”
Section: The Last Five-years Record Of a Multidisciplinary Journal Ofmentioning
confidence: 99%